Lone Parenthood in the Life Course - Dimitri Mortelmans (Life Course Research and Social Policies, 2017)
Lone parenthood is an increasing reality in the 21st century, reinforced by the diffusion of divorce and separation. This volume provides a comprehensive portrait of lone parenthood at the beginning of the XXI century from a life course perspective. The contributions included in this volume examine the dynamics of lone parenthood in the life course and explore the trajectories of lone parents in terms of income, poverty, labour, market behaviour, wellbeing, and health. Throughout, comparative analyses of data from countries as France, the United Kingdom, Ireland, Germany, Belgium, Sweden, Switzerland, Hungary, and Australia help portray how lone parenthood varies between regions, cultures, generations, and institutional settings. The findings show that one-parent households are inhabited by a rather heterogeneous world of mothers and fathers facing different challenges. Readers will not only discover the demographics and diversity of lone parents, but also the variety of social representations and discourses about the changing phenomenon of lone parenthood. The book provides a mixture of qualitative and quantitative studies on lone parenthood. Using large scale and longitudinal panel and register data, the reader will gain insight in complex processes across time. More qualitative case studies on the other hand discuss the definition of lone parenthood, the public debate around it, and the social and subjective representations of lone parents themselves. This book aims at sociologists, demographers, psychologists, political scientists, family therapists, and policy makers who want to gain new insights into one of the most striking changes in family forms over the last 50 years.